2016
DOI: 10.1038/ncomms10993
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-378 limits activation of hepatic stellate cells and liver fibrosis by suppressing Gli3 expression

Abstract: Hedgehog (Hh) signalling regulates hepatic fibrogenesis. MicroRNAs (miRNAs) mediate various cellular processes; however, their role in liver fibrosis is unclear. Here we investigate regulation of miRNAs in chronically damaged fibrotic liver. MiRNA profiling shows that expression of miR-378 family members (miR-378a-3p, miR-378b and miR-378d) declines in carbon tetrachloride (CCl4)-treated compared with corn-oil-treated mice. Overexpression of miR-378a-3p, directly targeting Gli3 in activated hepatic stellate ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
161
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(168 citation statements)
references
References 68 publications
6
161
1
Order By: Relevance
“…A recent study shows that miR-378a-3p, a negative regulator of TGFβ1, contributes to the suppression of cardiac fibrosis [16]. Hyun et al found that miR-378a-3p could suppress HSC activation by targeting Gli3 [17]. However, the biological role of miR-378a-3p in liver fibrosis remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study shows that miR-378a-3p, a negative regulator of TGFβ1, contributes to the suppression of cardiac fibrosis [16]. Hyun et al found that miR-378a-3p could suppress HSC activation by targeting Gli3 [17]. However, the biological role of miR-378a-3p in liver fibrosis remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…4 miR-378 suppress expression of Gli3 to inhibit activation of hepatic stellate cells and liver fibrosis. 18 However, a role of miR-378 in the regulation of skeletal muscle development has not been described.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, miRNAs have been found to be important regulators of osteogenic signaling pathways in multiple aspects and multiple signaling pathways. MiRNAs are short non-coding RNA molecules of 17-25 nucleotides that control gene expression at the post-transcriptional level and have been shown to play critical roles in a wide variety of biological processes, including proliferation, reprogramming, differentiation, cell cycle, invasion and apoptosis [6,7,9,[42][43][44]. Each miRNA regulates numerous mRNAs and involve multiple signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have been shown to play critical roles in a wide variety of biological processes, including proliferation, lineage commitment, differentiation, cell cycle, invasion and apoptosis [6][7][8][9][10]. Recently, increasing evidences have indicated that bone development and homeostasis is regulated by miRNAs [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%